Resection of carcinoma of the external auditory canal in a patient with a high jugular bulb using temporal craniotomy. Issue 3 (June 2021) - Matsumoto, Fumihiko; Miyakita, Yasuji; Sakai, Azusa; Akamatsu, Maki; Matsumoto, Yoshifumi; Matsumura, Satoko; Omura, Go; Kobayashi, Kenya; Narita, Yoshitaka; Yoshimoto, Seiichi
Abstract: External auditory canal (EAC) carcinoma is a rare and unusual malignancy. The complex anatomy and relationship between the tumor and surrounding tissues in a limited space render it difficult to attain safe resection margins during surgery. A high jugular bulb (HJB) is one such anatomical variation that has important surgical implications that complicate the surgical procedure for EAC carcinoma. A 73-year-old woman presented with a 3-month history of right ear pain. Pathological findings and computed tomography (CT) revealed EAC carcinoma, which was expanding to the middle ear (ME). Although there was no cavity inside the ME, an HJB was detected. Surgical treatment using a temporal incision for temporal craniotomy achieved complete resection of the tumor and preserved facial nerve function. The patient recovered without complications and was discharged 17 days after the operation. Temporal incision and temporal craniotomy is a useful approach for EAC carcinoma with HJB.